Pelatihan Olah Daging Ayam untuk Tingkatkan Pendapatan Keluarga di Majelling pada Kelompok Wanita Tani Mawar di Kelurahan Majelling, Sidenreng Rappang - Nurhidayah, Asma’ul Fitriana; Zulkarnaim, Zulkarnaim; Syamsudin, Syamsudin; Hasman, Hasman; Hasrin, Hasrin; Wulandari, Sri Helda; Yamin, Abdul Alim; Sari, Anggun Permata; Darmayanti, Darmayanti; Ananda, Tri Anugerah; Andriani, Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
Changes in lifestyle have led to a growing trend in the consumption of practical, fast, and nutritious foods, one of which is chicken kebabs. This community service activity aimed to enhance the skills and knowledge of the Mawar Women's Farmer Group in processing chicken meat into kebabs as both a family food alternative and a potential business opportunity. The program was conducted in Majelling Wattang Subdistrict, Maritenggae District, Sidenreng Rappang Regency. The methods employed included counseling, training, and hands-on practice using demonstrative and participatory approaches. Participants were introduced to techniques such as marination, cooking, condiment arrangement, and product packaging. The results showed a significant increase in participants’ understanding and technical skills, along with a growing interest in developing homemade kebab businesses. Approximately 80% of participants successfully produced kebabs of acceptable quality, and 10 participants expressed a commitment to start small-scale production. This program effectively contributed to strengthening household food security, empowering women, and promoting local economic development.